The Concept of Marketplace Marketing Strategy as Application of Marketing 4.0 - Dwi Yuda Syaputra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The development of the digital world, such as in the era of marketing 4.0, has found ways to make it easier for business people to sell their products. One of them is through online media or e-commerce. E-commerce acts as a complex sales medium which consists of sales, purchasing, payment, and online management activities. One of them is contained in a system that has been made in such a way as in the market. The research method used is to conduct a direct analysis of the Tokopedia.com marketplace through the website https://www.similarweb.com and through the analysis of the 5A framework approach to the application of marketing 4.0 as research indicators. The marketing strategy applied in the Marketing 4.0 era is a strategy that adapts to digital technology and current customer behavior. Networks on the internet are interconnected.